1997
DOI: 10.1094/pdis.1997.81.3.301
|View full text |Cite
|
Sign up to set email alerts
|

Two Groups of Phytoplasmas from Japan Distinguished on the Basis of Amplification and Restriction Analysis of 16S rDNA

Abstract: Phytoplasmas (mycoplasmalike organisms, MLOs) associated with mitsuba (Japanese hone-wort) witches'-broom (JHW), garland chrysanthemum witches'-broom (GCW), eggplant dwarf (ED), tomato yellows (TY), marguerite yellows (MY), gentian witches'-broom (GW), and tsu-wabuki witches'-broom (TW) in Japan were investigated by polymerase chain reaction (PCR) amplification of DNA and restriction enzyme analysis of PCR products. The phytoplasmas could be separated into two groups, one containing strains JHW, GCW, ED, TY, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Because OY and several 16Sr I-B group phytoplasma in Japan were reported to be transmitted by Macrosteles striifrons Anufriev (Okuda et al 1997), the transmissibility of RlWB phytoplasma by M. striifrons was also examined. About 100 nymphs of nonviruliferous M. striifrons in the second or the third instars fed on the young shoots of severely diseased C. ambigua for 24 h. After the acquisition access, about 50% of the nymphs had died, and the surviving nymphs were transferred and reared on healthy garland chrysanthemum plants.…”
Section: Insect Transmission Testmentioning
confidence: 99%
“…Because OY and several 16Sr I-B group phytoplasma in Japan were reported to be transmitted by Macrosteles striifrons Anufriev (Okuda et al 1997), the transmissibility of RlWB phytoplasma by M. striifrons was also examined. About 100 nymphs of nonviruliferous M. striifrons in the second or the third instars fed on the young shoots of severely diseased C. ambigua for 24 h. After the acquisition access, about 50% of the nymphs had died, and the surviving nymphs were transferred and reared on healthy garland chrysanthemum plants.…”
Section: Insect Transmission Testmentioning
confidence: 99%
“…Details of the original ¢eld-infected plants, vector relationships, and geographic origin were described previously [4]. Rice plants naturally infected with rice yellow dwarf (RYD) phytoplasma and healthy ones were collected at Kawachi, Tochigi Prefecture, Japan.…”
Section: Phytoplasma Strains and Sourcesmentioning
confidence: 99%
“…In the last decade, the phylogenic relationships among phytoplasmas and the phylogenic relationships between phytoplasmas and other prokaryotes have been established based on 16S rRNA sequences. These studies have classi¢ed the phytoplasmas into 14 groups [3] which are congruous with insect vector speci¢c-ity [4], and have shown that phytoplasmas are more closely related to acholeplasmas than any other mollicute [5]. On the other hand, very little is known about phytoplasma proteins, mainly because of the di¤culty in preparing phytoplasma-speci¢c proteins from infected plant or insect vector tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Culture methods for phytoplasmas have never been established (McCoy et al 1989). Through the introduction of molecular methods in plant mycoplasmology, it has become possible to determine the phylogenetic and taxonomic relations among phytoplasmas and between phytoplasmas and other prokaryotes (Lee et al 1998Okuda et al 1997;Seemüller et al 1994;Weisberg et al 1989). …”
mentioning
confidence: 99%
“…All samples, except paulownia witches' broom (PaW) strain, were maintained in Madagascar periwinkle [Catharanthus roseus (L.) G. Don] (Table 1) (Koike et al 1983;Okuda et al 1997). Paulownia plants (Paulownia tomentosa Thumb.)…”
mentioning
confidence: 99%